A critical analysis of the assumptions, aims and methods in Saward Hiltner's approach to pastoral counselling in the light of the major Christian traditions of pastoral care - Cook, Jonathan Thornhill (Department of Religious Studies, 2023)
In this study Seward Hiltner's approach to pastoral counselling is analysed on the basis of a number of criteria derived from a survey of the history of pastoral care. On the assumption that any trend in pastoral care which gained enough support from a wide enough section of the Church for a long enough period of time to warrant attention from recognised historians of pastoral care qualifies as a significant aspect of the tradition, the criteria take the form of questions arising from these trends. The questions are grouped so as to qualify or balance each other. The themes covered are those of discipline in the Church as both restoring the individual and protecting the Church; the definition of sin varying with the social role of the Church and providing both a boundary around the group and a code for individual guidance, while also representing an inner attitude; good and evil in human nature and the need for both absolute demand (including the provision of an ideal with which to identify the ideal self) and unlimited acceptance; the extent to which the pastor may exercise authority over the client; the need for both lay and ordained ministries; the scope of pastoral care, including the functions of healing, facilitating spiritual growth, sustaining, guiding, discipline, restoration, and liberating from oppressive institutions and customs; the need to provide people with a clear logic of belonging to God; and appropriate openness to the Christian tradition, secular social sciences and the sociopolitical context of the Church. On these criteria Hiltner's approach was found to have been well matched to the particular social context of America in the fifties, but to lack several aspects for the changed context of the present. These would either have to be accommodated in the counselling approach or be catered for in the pastoral context in which counselling should be offered. They include providing a demand both in the sense of a powerful ideal and a moral standard; integrating healing and sustaining in counselling with the other pastoral functions; reintroducing a sense of pastoral authority together with greater recognition of the role of lay ministry; providing a stronger and more explicit "logic of belonging"; and drawing more deeply on the pastoral traditions. Although there is overlap between the various criteria, it is suggested that they have proved useful in analysing Hiltner's approach and could be used to expose other approaches to the wisdom of the tradition. Suggestions are made for the development and use of the criteria in further research.